Pengaruh Ekstrak Rosella Terhadap Kualitas Es Krim Susu Kedelai - Putri, Mia Anggelina; Faridah, Anni; Fridayati, Lucy (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
This research has purpose to analyze the effect on the quality of roselleextract (color, texture, aroma, and flavor) soy milk ice cream. Rosella extract isused as much as 4%, 5%, 6% and 7% of the amount of soy milk. The research is acompletely randomized design experiment with three replications. The respondentis S1 and D3 of the Culinary department students about 30 students. Theindependent variable (X) which is 4% (X1), 5% (X2), 6% (X3), 7% (X4). While thedependent variable (Y) is the quality of soy milk ice cream. The data obtained andtabulated in tables and tested ANOVA, significantly different if followed byDuncan's test. Results of this research is the effect of roselle extract as much as4% (X1) gives less influence purple color, texture is rather smooth, somewhatberamoa soy milk, sweet taste, and less sour. While on treatment of 5% (X2) forquality some what purple color, texture is rather smooth, slightly scented soymilk, sweet, and slightly sour. In treatment 6% (X3) for the quality of the colorpurple, somewhat delicate texture, less flavorful soy milk, the taste is rather sweet,and sour. And at 7% (X4) for the quality of the color very purple, somewhatdelicate texture, less flavorful soy milk, the taste is rather sweet, and very sour.Effect of roselle extract 6% (X3) gives the best quality on soy milk ice cream.Kata Kunci : Pengaruh, Ekstrak Rosella, Es Krim Susu Kedelai